Operationalizing vulnerability and resilience interdependencies in drought risk management - Konak, Abdullah; Balta-Ozkan, Nazmiye; Shrimpton, Elisabeth A.; Jacobson, Michael Gregory; Winstead, Daniel; Nardocci, Adelaide Cassia; Sarmah, Tanaya; Mendiondo, Eduardo Mario (Springer, 2026)
Droughts, exacerbated by climate change, pose increasingly complex challenges for social-ecological systems worldwide. Traditional index-based methodologies capture vulnerability and resilience at an aggregate level but often overlook the nuanced ways in which these two constructs interact. To address this gap, this study introduces the Matrix-Based Drought Indicator System (MADIS) framework that operationalizes the interdependence between vulnerability and resilience at the indicator level. By distinguishing between coping, adaptive, and transformative capacities, the MADIS framework supports a more detailed assessment of how specific resilience indicators can mitigate different vulnerability factors. Two studies, online workshops with global drought experts and collaborative workshops focusing on small-scale farming communities in Pennsylvania, demonstrate how participatory methods can be used to identify and validate these interdependencies. Findings suggest that integrating indicator-level interdependencies leads to more refined risk categorizations, facilitates stakeholder consensus, and better informs targeted policy interventions. These case studies also reveal the drawbacks and implementation challenges of the MADIS framework. Ultimately, the MADIS framework contributes to a more dynamic view of resilience and social-technical-ecological systems analysis of climate change-related risk assessment. Future work will expand upon this approach by incorporating continuous temporal feedback, additional hazard indicators, and integration with social-technical-ecological systems analysis.
Keywords: 4101 Climate Change Impacts and Adaptation; 41 Environmental Sciences; Prevention; 13 Climate Action; Environmental Sciences; Drought risk management; Vulnerability; Resilience; Vulnerability–resilience interdependence; Indicator-based framework